Thermal hydrosilylation of olefin with hydrosilane. Preparative and mechanistic aspects - Jung, Dong Euy; Han, Joon Soo; Yoo, Bok Ryul (ELSEVIER SCIENCE SA, 2011)
The reaction of trichlorosilane (1a) at 250 degrees C with cycloalkenes, such as cyclopentene (2a), cyclohexene (2b), cycloheptene (2c), and cyclooctene (2d), gave cycloalkyltrichlorosilanes [CnH2n-1SiCl3: n = 5 (3a), 6 (3b), 7 (3c), 8 (3d)] within 6 h in excellent yields (97-98%), but the similar reactions using methyldichlorosilane (1b) instead of 1a required a longer reaction time of 40 h and afforded cycloalkyl(methyl) dichlorosilanes [CnH2n-1SiMeCl2: n = 5 (3e), 6 (3f), 7 (3g), 8 (3h)] in 88-92% yields with 4-8% recovery of reactant 2. In large (2, 0.29 mol)-scale preparations, the reactions of 2a and 2b with 1a (0.58 mol) under the same condition gave 3a and 3b in 95% and 94% isolated yields, respectively. The relative reactivity of four hydrosilanes [HSiCl3-mMem: m = 0-3] in the reaction with 2a indicates that as the number of chlorine-substituent(s) on the silicon increases the rate of the reaction decreases in the following order: n = 3 > 2 > 1 >> 0. In the reaction with 1a, the relative reactivity of four cycloalkenes (ring size = 5-8) decreases in the following order: 2d > 2a > 2c > 2b. Meanwhile linear alkenes like 1-hexene undergo two reactions of self-isomerization and hydrosilylation with hydrosilane to give a mixture of the three isomers (1-, 2-, and 3-silylated hexanes). In this reaction, the reactivity of the terminal 1-hexene is higher than the internal 2- and 3-hexene. The redistribution of hydrosilane 1 and the polymerization of olefin 2 occurred rarely under the thermal reaction condition. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: TERT-BUTYL PEROXIDE; CATALYSIS; COMPLEX; IRRADIATION; ALKYNES